Structure and properties of composites (New York, 1993)
This book provides an authoritative source of information on the physical background of structure/property relationships in composite materials. First, the book presents fibers and whiskers as well as composites based upon polymeric, metal, and ceramic matrices. It examines the processing, structure, and properties of these three classes of materials with their renforcements in the form of particulates, whiskers, short fibers, and continuous fibers. Second, the book focuses on the interface in composites. It treats this subject under the premise that the term "interface" actually refers to a three-dimensional "interface" region, where the chemical, physical, and morphological features are different from in the bulk fiber and matrix phases. Finally, the book focuses on the modeling and characterization of the properties of composites, including elastic behavior, inelastic behavior, strength, fracture, and fatigue
Keywords: composite materials,fibrous composites,polymeric composites,strength of materials